Validity and reliability of pre-service teachers and teachers’ self-efficacy: a scoping review / Riyan Hidayat ... [et al.] - Hidayat, Riyan; Mohd Ayub, Ahmad Fauzi; Abd Hamid, Harris Shah; Nasir, Nurihan (Universiti Teknologi MARA, 2025)
Self-efficacy is defined as an individual’s belief in their capacity to organize and carry out the actions required to attain objectives. Academic research has consistently highlighted the increasing significance of self-efficacy for both pre-service and in-service teachers. This scoping review provides a detailed overview of the evaluation of self-efficacy among pre-service and inservice teachers, focusing on the validity measurement approaches, reliability assessment methods, and specific contextual applications. This research reviewed papers in the Scopus, Education Resources Information Centre (ERIC), and ScienceDirect databases regardless of years. From an initial pool of 22,053 documents, 40 studies met the eligibility criteria and were included in the review. The findings show that content and construct validity were frequently emphasized in the research methodologies. Internal consistency coefficients were the most used method for evaluating the reliability of measurement scales. Most studies concentrated on the broader educational field. This review highlights the necessity of a nuanced and comprehensive approach to validity assessment in research on teacher self-efficacy. Keywords: Reliability, Self-Efficacy, Scoping Review, Validity